Field evaluation of a geotextile filter for stormwater runoff control. Issue 4 (1st April 2015) - Hatipoglu, M.; Davis, A. P.; Franks, C.; Myers, R.; Koebler, J.; Aydilek, A. H.
Abstract : ABSTRACT: As urbanisation and land development rapidly increase, water quality stress due to urban stormwater runoff is becoming an increasingly prominent problem. Although a variety of technologies exist to improve urban runoff quality, ultra-urban areas pose a specific challenge. Geotextile filters, which are easy to maintain and have a long lifespan, can be an alternative to sand filters in urban areas as demonstrated in previous laboratory studies. This study examines the field effectiveness of a geotextile filter as a means of stormwater runoff treatment in Maryland. The results indicate that the filter is able to significantly reduce total suspended solids (TSS) concentrations in parking lot stormwater. Of the 18 storms analysed for TSS, 16 demonstrated an event mean concentration (EMC) less than the target value of 25 mg/l. However, no significant reduction of total phosphorus EMC occurred through the filters. Porosities and characteristic pore opening sizes of the field-exhumed geotextiles dropped 65–82%, accompanied by comparable permittivities; however, the final hydraulic conductivities of the field-exhumed geotextiles were still 25 times higher than that of a typical unclogged uniform sand. Stormwater TSS geotextile modelling developed in an earlier study was successful in predicting hydraulic conductivity decrease in the field.